Evaluation of the effect of jaw shape/size options in a new brand of digital panoramic machine on the accuracy of linear and angular measurements - Mehrdad Abdinian; Reyhaneh Faghihian; Farnaz Farhad (Wolters Kluwer Medknow Publications, 2016)
Introduction: Although placement of structures within the focal trough is important, image sharpness is affected by other factors such as the shape and size of the jaw in panoramic machines. The aim of this study was to evaluate the effect of jaw shape/size options in a digital panoramic machine on the accuracy of linear and angular measurements. Materials and Methods: In this in vitro study, one dry human skull was chosen, and hypothetical tooth positions were determined. Horizontal, vertical, and angular dimensions were indicated by gutta-percha in tooth positions and assessed by two observers. After determining jaw shape and size, standard panoramic radiographs were obtained in 6 positions by changing the focal trough shape and with two other shapes and one larger size of the jaw. Linear and angular measurements were made by two separate observers individually on each radiograph. Statistical analysis was performed by SPSS 20. Intraclass correlation coefficient (ICC) and paired t-test were used for data analysis. Results: According to ICC values, inter-observer correlations for radiographic measurements and for physical measurements were 0.994 and 0.995, respectively (P < 0.001). There were significant differences between vertical and angular measurement son one hand and actual measurements on the other (P < 0.05); however, the difference between horizontal and actual measurements was not significant (P > 0.05). Conclusions: The results of the present study indicated that vertical and angular measurements were clinically reliable with all the options. However, jaw size and shape options which changed the focal trough did not improve the accuracy of horizontal measurements.